Leverage and asset prices: An experiment - Marco Cipriani; Ana Fostel; Daniel Houser (Federal Reserve Bank of New York, 2012)
This is the first paper to test the asset pricing implication of leverage in a laboratory. We show that as theory predicts, leverage increases asset prices: When an asset can be used as collateral (that is, when the asset can be bought on margin), its price goes up. This increase is significant, and quantitatively close to what theory predicts. However, important deviations from the theory arise in the laboratory. First, the demand for the asset shifts when it can be used as a collateral, even though agents do not exhaust their purchasing power when collateralized borrowing is not allowed. Second, the spread between collateralizable and noncollateralizable assets does not increase during crises, in contrast to what theory predicts.
Keywords: A10; C90; G12; 330; leverage; asset pricing; experimental economics